2018
DOI: 10.1016/j.chb.2017.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating spatial distance in virtual reality: Effects on treadmill walking performance in patients with intermittent claudication

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…With the rapid development of science and technology, VR has become a hot topic in various fields in recent years, including games (Zyda, ), business (Van Kerrebroeck, Brengman, & Willems, ), social networking (Ip et al , ), medical treatment (Cuperus et al ., ; Dubovi et al ., ; Lorenzo, Lledó, Pomares, & Roig, ) and education (Merchant et al , ; Passig, Tzuriel, & Eshel‐Kedmi, ; Sánchez, Barreiro, & Maojo, ). Many studies have reported the advantages of VR, as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the rapid development of science and technology, VR has become a hot topic in various fields in recent years, including games (Zyda, ), business (Van Kerrebroeck, Brengman, & Willems, ), social networking (Ip et al , ), medical treatment (Cuperus et al ., ; Dubovi et al ., ; Lorenzo, Lledó, Pomares, & Roig, ) and education (Merchant et al , ; Passig, Tzuriel, & Eshel‐Kedmi, ; Sánchez, Barreiro, & Maojo, ). Many studies have reported the advantages of VR, as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Screenshots of VR applications for special needs education: Left: User interacting with components of VR system [122]. Middle and Right: VR environment that participants moved through while walking on the treadmill [123].…”
Section: Special Needs Educationmentioning
confidence: 99%
“…The authors of [126] describe the technologies and original designs available at LIRKIS Laboratory and their relation to the disabled people education. In [123], the authors investigate whether manipulations of spatial distance in VR can influence treadmill exercise performance in patients with intermittent claudication; a cramping pain or discomfort in the legs, which occurs during exercise. Ravi et al [127] evaluate the effectiveness of VR systems used in the motor rehabilitation of children with cerebral palsy.…”
Section: Special Needs Educationmentioning
confidence: 99%
“…What they have in common is that their effects are the direct result of a mismatch between false visual feedback and somatosensory/proprioceptive feedback. In contrast to this, Cuperus et al tested a perceptual illusion that relies on a mismatch between a manipulated VR environment and a weakness of memory for a similar, previously experienced environment [17]. Participants in their study were patients with intermittent claudication; a cramping pain or discomfort in the legs, which occurs during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Cuperus et al [17] indicated great potential for the use of memory-related perceptual illusions to influence clinically relevant physical activity. In the present study, we assessed whether these findings generalize to healthy individuals, because patients with intermittent claudication typically have several comorbid conditions that may affect memory.…”
Section: Introductionmentioning
confidence: 99%